Customer data protection mitigations: Building Baitul Mal wa Tamwil transaction data security system in Lampung - Ambarwati, Diana; Hermanita, Hermanita (Universitas Islam Indonesia, 2023)
IntroductionData security is a critical issue in today's digital age, exacerbated by the rampant online buying and selling of consumers’ personal data. This study focuses on the strategies employed by microfinance institutions, specifically Baitul Maal wa Tamwil (BMT), to protect member data and manage the associated risks.ObjectivesThe objective of this study is to describe mitigation strategies for data protection and risk management implemented by BMTs in Lampung. MethodThis field research employs qualitative methods, including observation and interviews, which are analyzed using the inductive thinking paradigm. Data collection focuses on BMTs' risk management practices and their cooperation with commercial banks to transfer risk.ResultsThe findings reveal that BMTs in Lampung have implemented effective risk-management strategies for data protection. Some BMTs transfer risk to commercial banks, a strategy known as risk transfer. Others adopt risk reduction and acceptance strategies by enhancing data security, training employees on system use, and managing existing risks to minimize business impact. ImplicationsThis study highlights the importance of robust data protection and risk management strategies to maintain customer trust in microfinance institutions. Effective risk mitigation ensures customer data security, thereby enhancing the credibility and sustainability of BMTs.Originality/NoveltyThis study contributes to the understanding of data security practices in microfinance institutions, particularly in the context of Islamic microfinance, by exploring practical mitigation strategies and their implementation.